KEBIJAKAN PEMBERIAN REMISI KEPADA NARAPIDANA TINDAK PIDANA KORUPSI DI LEMBAGA PEMASYARAKATAN KLAS II B SLEMAN - SURYA, ACHMAD ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Granting remission to prisoners of corruption government regulation No. 28 of 2006 concerning the change of government regulation No. 32 in 1999 about the terms and procedure for implementation of the rights of prisoners. For inmates of corruption, given remission after serving criminal third 1/3 (one-third) of the criminal and good behavior. This is different with remissions for the common criminal prisoners. Research was conducted in correctional institutions of class II B Sleman. As for the purpose of research to find practical implimentation of remissions for prisoners of curruption in correctional institutions of class II B Sleman and know the views of police and prosecutors as an investigator of corruption agianst the policy of granting remission to prisoners of corruption in correctional institutions of class II B Sleman. This research is a normative empirical research, using secondary data as the data originally obtained from the literature study and then continued with the primary data in the form of direct interviews or data from field research. Data obtained were analyzed by qualitative descriptive methods, namely by way of explaining or describing something that is derived from theories relating to research, applicable regulations and the realities that occur on the object of research precisely and clearly. Results showed that remissions for corruption in correctional institutions of class II B Sleman in accordance with government regulations No. 28 of 2006 regarding change in government regulation No. 32 of 1999 on the terms and procedure of prisoners and majority of speakers objected to the granting remission to prisoners of corruption. They reasoned corruption differ from ordinary crimes. Only one informant who agreed to granting remission to prisoners in corruption, by reason of remission is the right of every inmate.